Profile and Appropriateness of Antibiotic Use Among Outpatients with Respiratory Tract Infections at the Pagantenan Subdistrict Community Health Center - Zakaria Zakaria; Lisa Narulita; Sufiyatin Riski Adawiyyah; Akhmad Fathir (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Acute respiratory tract infections are common health conditions requiring appropriate antibiotic selection and supportive treatment according to patient symptoms and clinical diagnosis. Specific Background: Outpatient treatment involves different antibacterial agents, formulations, doses, and adjunctive therapies, particularly among patients diagnosed with pharyngitis and tonsillitis. Knowledge Gap: Local descriptive evidence integrating patient characteristics, diagnostic patterns, antibiotic distribution, and supportive medication use remains limited within community health center settings. Aims: This study aimed to identify patient characteristics and describe antibiotic and supportive treatment profiles among patients with respiratory tract infections. Results: A retrospective descriptive analysis of 58 medical records showed that female patients represented 53% of cases, while tonsillitis was the most frequent diagnosis at 66%, compared with pharyngitis at 34%. Amoxicillin was the most frequently recorded antibiotic, accounting for 77.58% of antibacterial therapy, followed by cefadroxil, co-trimoxazole, and erythromycin. Supportive treatment included analgesic-antipyretics, antihistamines, cough medicines, corticosteroids, and vitamins, with paracetamol 500 mg recorded most frequently among adjunctive medications. Novelty: The study presents an integrated outpatient profile combining demographic characteristics, diagnoses, antibiotic selection, dosage forms, and supportive therapies within one retrospective dataset. Implications: The findings provide baseline information for reviewing medication selection, strengthening antibiotic monitoring, and planning symptom-based pharmaceutical services in primary healthcare. Highlights: Female patients represented 53% of the 58-record sample. Tonsillitis accounted for 66%, compared with 34% for pharyngitis. Paracetamol 500 mg was the most frequently documented adjunctive therapy. Keywords: ISPA, Treatment Profile, Community Health Center, Antibiotics, Drugs